The Application of Progressive Muscle Relaxation Therapy to Reduce Signs and Symptoms in Patients at Risk of Violent Behavior at dr. RM. Soedjarwadi Regional Mental Hospital - ‘Ainin, Shiba Qurrotu; Diktina, Amalia Arifatul; Reknoningsih, Wahyu (Al-Hijrah Indonesia, 2025)
Background: Risk for Violent Behavior (RPK) refers to aggressive actions that may result in harm to oneself or others, often triggered by unmet needs, perceived failure, frustration, or ineffective stress management. Non-pharmacological interventions play a crucial role in managing such behaviors, and one effective approach is Progressive Muscle Relaxation (PMR) therapy. Objective: This study aims to evaluate the effectiveness of Progressive Muscle Relaxation therapy in reducing signs and symptoms of violent behavior among patients at risk of aggression at Dr. RM. Soedjarwadi Regional Mental Hospital, Central Java. Methods: A descriptive case study design was employed, incorporating a pre-test and post-test approach using the RUFA (Rating Unit for Aggressive Behavior) observation sheet to assess changes in violent behavior. Two respondents were observed before and after the intervention. Results: Prior to the intervention, both respondents exhibited moderate levels of violent behavior, classified as Intensive Stage II, with baseline scores of 11 and 14, respectively. Following three consecutive days of PMR therapy, both respondents showed improvement, transitioning to Intensive Stage I (mild), with post-intervention scores of 8 and 9. Conclusion: Progressive Muscle Relaxation therapy demonstrates a positive impact in reducing violent behavior among psychiatric patients. The findings indicate a noticeable reduction in aggression levels after the intervention, suggesting that PMR is an effective non-pharmacological strategy for managing patients at risk of violent behavior.